Denture Hygiene Knowledge and Practices among Complete Denture Wearers attending a Postgraduate Dental Institute - Saxena, Sudhanshu; Gowd, Snigdha; Shankar, Thatapudi; Suresan, Vinay; Mantri, Sneha; Mishra, Prateek; Panday, Pragya (The journal of contemporary dental practice, 2017)
The aim of this study was to assess the denture hygiene knowledge and practices among patients using complete dentures attending a postgraduate dental hospital in Jabalpur city. The objective of this study was to assess the relationship between hygiene knowledge and practices to the denture wearer's gender, education, and income. A descriptive, cross-sectional survey was conducted using a self-administered questionnaire involving the complete denture patients attending the Department of Prosthodontics. The study subjects were randomly selected by recruiting old dentures wearers visiting the Department of Prosthodontics for a recall visit or for new dentures on the odd dates of the month. All subjects signed an informed consent before filling the questionnaire. The institutional review committee approved the study. Descriptive statistics included computation of frequencies and percentages. Nonparametric test, namely, chi-square test, was used for further data analysis; p-value <0.05 was considered statistically significant. A total of 530 individuals were approached for participation in our survey, 30 (5.66%) subjects declined to participate. The results showed that 195 (39%) subjects were wearing the same dentures for more than 5 years. In this study, 51 (10.2%) subjects reported never having been advised by their dentists as to how to clean their dentures. Among all the subjects interviewed, 264 (52.8%) reported to clean the oral tissues daily. This study disclosed that 66 (13.2%) of the subjects usually slept with their dentures. Maximum subjects in illiterate group had experienced bad breath sometimes when compared with subjects in postgraduate group (χ = 47.452, p < 0.001). There was a significant difference for method of denture cleaning according to gender (χ = 101.076, p < 0.001). The majority of the denture wearers have limited knowledge of denture cleansing and oral hygiene practices. Hygiene habits and practices may not always present a positive correlation with the gender, educational level, and income of the subjects. Periodic recall for evaluation of denture and mucosal surfaces along with reinforcement of denture hygiene instructions will go a long way in helping the patients reap maximum benefits out of their prostheses.